Inspiratory time and tidal volume during intermittent positive pressure ventilation. - Field, D (1985)
We measured the tidal volume achieved during intermittent positive pressure ventilation using various inspiratory times with a minimum of 0.2 seconds. Results indicate that tidal volume shows no reduction with inspiratory times down to 0.4 seconds. An inspiratory time of 0.3 seconds, however, is likely to reduce tidal volume by 8%, and at 0.2 seconds a 22% fall may be anticipated.